Flow Cytometric Monitoring of Antibiotic-Induced Injury in Escherichia coli Using Cell-Impermeant Fluorescent Probes - Mortimer, Fiona C. (American Society for Microbiology, 2000)
Three fluorescent nucleic acid binding dyes—propidium iodide, TO-PRO-1, and SYTOX green—were evaluated, and their abilities to distinguish between bacterial cells with and without an intact cytoplasmic membrane were compared. Each dye was readily able to discriminate between healthy and permeabilized cells of Escherichia coli, although SYTOX green showed a greater enhancement in fluorescence intensity on staining-compromised, as opposed to healthy, cells in log-phase growth, than either PI or TO-PRO-1. Flow cytometric analysis of E. coli stained with these dyes after exposing them to several antimicrobial agents showed that all three dyes were able to detect antimicrobial action. Notably, however, the intensity of the cell-associated fluorescence was related to the mechanism of action of the antimicrobial agent. Large changes in fluorescence intensity were observed for all the dyes subsequent to β-lactam antibiotic action, but smaller changes (or no change) were seen subsequent to exposure to antimicrobials acting directly or indirectly on nucleic acid synthesis. Furthermore, cell-associated fluorescence did not relate to loss of viability as determined by plate counts. Despite offering much insight into antimicrobial mechanisms of action, these fundamental problems become relevant to the development of rapid antimicrobial susceptibility tests if colony formation is used as the standard.